Update on the current occurrence of two rare fern species in Sicily (Italy): Dryopteris affinis (Lowe) Fraser-Jenk. and D. robusta (Oberh. et Tavel ex Fraser-Jenk.) P. D. Sell. in the Peloritani Mountains - Kozlowski, Gregor; Freigang, Jens; Pasta, Salvatore; Guarino, Riccardo; Anania, Francesco; Champoud, Luca; Garfì, Giuseppe; Gristina, Alessandro Silvestre; Marcenò, Corrado; Picone, Rosa Maria; Crisafulli, Alessandro (Mediterranean Botany, 2025)
The Dryopteris affinis species complex has a predominantly European distribution. The taxonomy and distribution of the Mediterranean taxa belonging to this complex are poorly studied and not fully understood. This paper provides new information on the occurrence and distribution of two taxa belonging to the D. affinis complex in Sicily, following the 2021 discovery of a new population in the Peloritani Mts in the Cataolo Valley. The new population is composed of approximately 15 individuals. Plant material (7 individuals) was collected in May 2024 along an altitudinal gradient ranging from 1070 to 1120 m a.s.l. A detailed morphological investigation, genome size analysis and ploidy level estimation were conducted for all of the sampled plants. Two individuals were identified as belonging to the diploid D. affinis subsp. affinis var. affinis, whereas the remaining 5 individuals were identified as triploid D. robusta. The confirmation of the presence of D. affinis in Sicily and the first finding of D. robusta on the island proves the key role played by the Peloritani Mts. as a refuge for species with a mid-European and boreal range.